1981
DOI: 10.1254/jjp.31.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the chronotropic responses to local anesthetics (procaine, lidocaine, prilocaine, mepivacaine and bupivacaine) of the canine sinus node in situ.

Abstract: Abstract-Effectsof local anesthetics (procaine, lidocaine, prilocaine, mepivacaine and bupivacaine) on the sinus node of the nerve-intact dog heart were studied in situ by means of selective perfusion of the sinus node through the sinus node artery. The agents caused a dose-dependent decrease in heart rate and the order of their potency in decreasing the heart rate was as follows, bupivacaine>lidocaine=mepivacaine=prilocaine> procaine. The decrease in heart rate produced by these local anesthetics was not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…For lidocaine the concentrations could be increased up to 100 µM until the cells stopped beating. In accordance with literature data, application of lidocaine did not result in an increase of frequency but rather in a decrease [64,65].…”
Section: Nasupporting
confidence: 92%
“…For lidocaine the concentrations could be increased up to 100 µM until the cells stopped beating. In accordance with literature data, application of lidocaine did not result in an increase of frequency but rather in a decrease [64,65].…”
Section: Nasupporting
confidence: 92%
“…In the atrium-isolated preparation cocaine decreases the rate of contractibility in a monoamine-independent manner (Trendelenburg, 1968). Similarly, procaine decreases heart rate when delivered directly at the sinoatrial node through the sinus node artery (Satoh, 1981). The negative chronotropic effect of procaine on sinoatrial cells is a combination of blockade of sodium and potassium conductances (Satoh and Hashimoto, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent concentrations impair slow AP conduction through depolarized canine Purkinje fibres (Lamanna et al, 1982). Higher concentrations of lidocaine (2 x 10-4 M) depress the electrical activity that depends on slow inward currents, as in rabbit sinus node cells (Satoh & Hashimoto, 1984) and in canine nodal cells (Satoh, 1981). On the other hand, it has been shown that lidocaine suppresses depressed fast responses, but has little or no effect on slow APs on canine Purkinje fibres (Brennan et al, 1978) and on guineapig atrial muscle (Hashimoto et al, 1979).…”
Section: Comparison With Verapamilmentioning
confidence: 99%